Smart Home and Ambient Assisted Living Based on the Internet of Things - H. Sayuti; R. A. Rashid; N. M. Abdul Latiff; M. R. Abdul Rahim; A. H. F. Abdul Hamid; M. A. Sarijari; N. E. Ghazali (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper presents a Smart Home and Ambient Assisted Living (SHAAL) system that has been developed and tested in a real experimental home environment. SHAAL system is designed on wireless sensor network (WSN) linked to the cloud network on the Internet. The development of SHAAL is divided into two phases: the design of SHAAL network and the development of SHAAL applications. SHAAL network is made up of the home network which is the WSN, and the cloud network. The network is designed using TelG mote that operates under Zigbee technology and includes various sensor modules for SHAAL system. The cloud network consists of the gateway, the server and user devices running on third generation (3G) network. Using priority scheduling algorithm for data transmission, it is shown that the performance delay of this system on the test-bed experiment is 34.2 percent less compared to the theoretical study. The implementation of the experimental testbed has proven that SHAAL has been successfully designed and deployed in the real world.